Cohesion, Flexibility and Family Support in Relation to the Psychological Wellbeing of Individuals with Obesity Issues - González Sotomayor, Roxana; Ruíz Martínez, Ana Olivia; González Arratia López Fuentes, Norma Ivonne; Oudhof-van Barneveld, Hans; Vázquez Arévalo, Rosalía (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
Obesity is a multi-causal disease which is increasing worldwide and fosters multiple maladjustments in the biological, psychological, family and social wellbeing in obese people. There are several family related factors, such as family interaction and support, which are directly related to the increase or decrease of obesity and wellbeing. Thus, the objective of this investigation was: analyze the incidence of BMI, cohesion, family flexibility and socio-family support, towards the psychological wellbeing in obese people. Scale of Wellbeing, Faces III Test, Scale of Perceived Family and Friends Social Support were the tools applied to 350 people presenting obesity issues. Results showed a tendency for extreme scores in the factors of cohesion and flexibility related to dysfunctional family relations. Acute differences were noticed between men and women in regards to family cohesion, family support and social-family support; obese men scored much higher than women. Predictive models indicate that family cohesion in women and social support in men, have a direct effect on their psychological wellbeing. This results could be of great help in intervention programs which focus on a specific sex and include family and social factors